The James Supportive Care Screening: integrating science and practice to meet the NCCN guidelines for distress management at a Comprehensive Cancer Center. Issue 9 (25th February 2013) - Wells‐Di Gregorio, Sharla; Porensky, Emily K.; Minotti, Matthew; Brown, Susan; Snapp, Janet; Taylor, Robert M.; Adolph, Michael D.; Everett, Sherman; Lowther, Kenneth; Callahan, Kelly; Streva, Devita; Heinke, Vicki; et al.
Abstract: Background: Selecting a measure for oncology distress screening can be challenging. The measure must be brief, but comprehensive, capturing patients' most distressing concerns. The measure must provide meaningful coverage of multiple domains, assess symptom and problem‐related distress, and ideally be suited for both clinical and research purposes. Methods: From March 2006 to August 2012, the James Supportive Care Screening (SCS) was developed and validated in three phases including content validation, factor analysis, and measure validation. Exploratory factor analyses were completed with 596 oncology patients followed by a confirmatory factor analysis with 477 patients. Results: Six factors were identified and confirmed including (i) emotional concerns; (ii) physical symptoms; (iii) social/practical problems; (iv) spiritual problems; (v) cognitive concerns; and (vi) healthcare decision making/communication issues. Subscale evaluation reveals good to excellent internal consistency, test–retest reliability, and convergent, divergent, and predictive validity. Specificity of individual items was 0.90 and 0.87, respectively, for identifying patients with DSM‐IV‐TR diagnoses of major depression and generalized anxiety disorder. Conclusions: Results support use of the James SCS to quickly detect the most frequent and distressing symptoms and concerns of cancer patients. The James SCS is an efficient, reliable, and valid clinical and research outcomes measure. Copyright © 2013 John Wiley & Sons, Ltd.